Microbial Fuel Cell Technology for Bioelectricity - Sivasankar, Venkataraman; Mylsamy, Prabhakaran; Omine, Kiyoshi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
In view of the increased consumption of energy due to the proliferation of electronic devices, this book addresses the trends, similarities, differences and advances in fuel cells of both chemical and biological composition. Fundamentals of microbial fuel cells are described, accompanied by details surrounding their uses and limitations. Chapters on electricigens, microbial group investigations and performance, Rumen Fluid microbes and state-of-the-art advances in microbial fuel cell technology are discussed. The book elaborates upon analytical techniques used for biofilm characterization. It also includes chapters on MFC models that include plant-based MFCs, Algal/Fungi MFCs, MDCs and MFCs using animal waste. A critical review on the performance of MFC technology in field trials is offered in an exclusively dedicated section. By addressing one of the most promising sources for clean and renewable energy, this book fills a pressing need to understand a possible solution for meeting the energy demands in our highly advanced technical world.
Chapter 1. Renewable biological sources of energy: Potentials, Progress and Barriers -- Chapter 2.Microbial fuel cell: Fundamentals, types and significance -- Chapter 3.Plant microbial fuel cell technology: Developments and limitations -- Chapter 4.Current advances in Paddy plant microbial fuel cell -- Chapter 5.Algal microbial fuel cells - Promising green energy generators -- Chapter 6.Fungal Fuel Cells - Nature's perpetual energy resource -- Chapter 7.Bio-electricity generation in soil microbial fuel cell using organic waste -- Chapter 8.Microbial fuel cell research using animal waste: A feebly explored area to others -- Chapter 9.Electricigens: Role and prominence in microbial fuel cell performance -- Chapter 10.Rumen fluid microbes for bioelectricity production - A novel approach -- Chapter 11.Advances in concurrent bio-electricity generation and bio-remediation through microbial fuel cells -- Chapter 12.Microbial Desalination Cell - A promising area in microbial fuel cell technology -- Chapter 13.The performance of microbial fuel cells in field trials - A global perspective -- Chapter 14.Future perspectives on cost - effective microbial fuel cells in rural areas.
Keywords: Biomaterials; Energy harvesting; Renewable energy sources; Biomaterials; Energy Harvesting; Renewable Energy